Microparticles: Compartmentalized Spherical Collagen Microparticles for Anisotropic Cell Culture Microenvironments (Adv. Healthcare Mater. 8/2017). Issue 8 (19th April 2017) - Yoshida, Satoru; Takinoue, Masahiro; Onoe, Hiroaki
Abstract : A new fabrication method for obtaining anisotropic hydrogel microparticles (approximately 100 μm in diameter) with different types of ECM hemispheres is proposed by Hiroaki Onoe and co‐workers in article number1601463 to mimic the microenvironments observed in in vivo. This fabrication method enables gaining control of the hemispherical volume, density, and type of ECM. The proposed microparticles can be utilized for cell culture in anisotropic microenvironments.